2018
DOI: 10.1080/10717544.2018.1440669
|View full text |Cite
|
Sign up to set email alerts
|

Multiseed liposomal drug delivery system using micelle gradient as driving force to improve amphiphilic drug retention and its anti-tumor efficacy

Abstract: To improve drug retention in carriers for amphiphilic asulacrine (ASL), a novel active loading method using micelle gradient was developed to fabricate the ASL-loaded multiseed liposomes (ASL-ML). The empty ML were prepared by hydrating a thin film with empty micelles. Then the micelles in liposomal compartment acting as ‘micelle pool’ drove the drug to be loaded after the outer micelles were removed. Some reasoning studies including critical micelle concentration (CMC) determination, influencing factors tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Zhang et al and Franzè et al both demonstrated a more sustained drug release from MIL than from micelles as we found in our research. However, neither of these two other papers provided a cryo-TEM image or other direct evidence to verify that the micelles were actually inside the aqueous core of the liposomes [ 33 , 34 ]. While Romana et al did provide a cryo-TEM image of a single liposome containing worm-like micelles inside, no ratio of liposomes containing micelles over all liposomes was reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al and Franzè et al both demonstrated a more sustained drug release from MIL than from micelles as we found in our research. However, neither of these two other papers provided a cryo-TEM image or other direct evidence to verify that the micelles were actually inside the aqueous core of the liposomes [ 33 , 34 ]. While Romana et al did provide a cryo-TEM image of a single liposome containing worm-like micelles inside, no ratio of liposomes containing micelles over all liposomes was reported [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 20 μL of drug-loaded mPEG- b -PCL micelle solution was dissolved in 180 μL of ACN. The encapsulation efficiency (EE, %) and drug loading (DL, %) of DTX and OTH were calculated by using the equation below [ 54 , 55 , 56 ]: DL% = Weight of drug in micelles/weight of feeding drug and polymer × 100 EE% = Weight of drug in micelles/weight of feeding drug × 100 …”
Section: Methodsmentioning
confidence: 99%
“…Collagenase (CLG) can effectively destroy collagen and destroy dense ECM. [ 143 ] In an oxygenated nanosystem containing CLG (FePO 2 @HC), under the action of GSH, FePO 2 @HC can release CLG, destroy the dense structure of the ECM, promote FePO2 into the deep part of the tumor, release oxygen to alleviate hypoxia and promote the formation rate of ROS. [ 144 ] It has been proven that destroying the dense structure of the ECM can enhance the therapeutic effect of SDT, and this result mainly comes from the improvement of the penetration of the nanodrug delivery system.…”
Section: Tme and Tme‐related Sdtmentioning
confidence: 99%
“…Collagenase (CLG) can effectively destroy collagen and destroy dense ECM. [143] In an oxygenated nanosystem containing CLG (FePO 2 @HC), under the action of GSH, FePO 2 @HC can release CLG, destroy the a-c) Reproduced with permission. [124] Copyright 2020, American Chemical Society.…”
Section: Dense Ecm In the Tme And Sdt Combined With Ecm Degradationmentioning
confidence: 99%